Role of heterotrigona itama bee bread on reproductive system in male rats fed with high-fat diet - Suleiman, Joseph Bagi (2020)
Obesity has been reported to cause testicular oxidative stress, inflammation and apoptosis thereby resulting in impaired male reproductive function while bee bread, on the other hand, exhibits antioxidant, anti-inflammatory and anti-apoptotic properties as seen in other tissues. However, to date, the role of Heterotrigona itama bee bread on male reproductive system in obesity has not been reported. Therefore, the objectives of this study were (i) to assess pH, composition and antioxidant properties of Heterotrigona itama bee bread and (ii) to determine the role of Heterotrigona itama bee bread on anthropometric parameters, sperm parameters, testicular oxidative stress, inflammation, apoptosis, sexual behaviour as well as reproductive performance in male rats fed with high-fat diet (HFD). Thirty-two adult male Sprague Dawley rats weighing between 250-300 g were randomised into four groups (n=8/group), namely normal control (NC), HFD, HFD plus bee bread (HFD+B) and HFD plus an anti-obesity drug orlistat (HFD+O) groups. Bee bread (0.5g/kg/day) and orlistat (10 mg/kg/day) were suspended in distilled water and given by oral gavage for 12 weeks. During the tenth week, each male rat was cohabited with a fertile female rat to assess male sexual behaviour and reproductive performance. At the end of 12 weeks, male rats were anaesthetized and blood, as well as the reproductive organs, were removed for the determination of reproductive functions. Bee bread was acidic, had in vitro antioxidant properties and nine phenolic compounds. Bee bread significantly improved the anthropometric parameters and lipid profile in rats fed with HFD. Similarly, bee bread also significantly ameliorated testicular oxidative stress, inflammation, apoptosis and germ cell proliferation in rats fed with HFD. Furthermore, bee bread significantly enhanced sperm count, viability, motility, and reduced abnormal sperm morphology as well as fragmented nDNA. In addition, bee bread significantly increased the levels of reproductive hormones and penile cyclic guanosine monophosphate, and decreased leptin level, thereby increasing the number of rats with improved intromission and ejaculation as well as mating and fertility indices. In conclusion, bee bread significantly improved the reproductive system in male rats fed with HFD by attenuating testicular oxidative stress, inflammation, apoptosis and improving testicular germ cell proliferation. However, further studies are needed to further investigate the molecular mechanism of action of bee bread and to determine its safety via toxicity study before it is used as a complementary treatment among obese patients.